PENGARUH LABELISASI HALAL DAN HALAL AWARENESS TERHADAP KEPUTUSAN PEMBELIAN KOREAN FOOD PADA GEN-Z MUSLIM JAWA TIMUR - Cahyati, Anisa Nur; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2024)
Halal products are a necessity for Muslim consumers. The concept of halal in a product is not only based on its composition but must also be hygienic, clean, and of good quality. The aim of this research is to analyze the influence of halal labeling and halal awareness on Korean Food purchasing decisions among Gen-Z Muslims in East Java. The research method uses quantitative methods with primary data sources obtained from distributing questionnaires online. Sampling used purposive sampling technique with a total of 110 respondents. The technique used in data analysis is multiple linear regression analysis with the SPSS-23 analysis tool. The results of the research show that halal labeling has no influence on purchasing decisions, halal awareness influences purchasing decisions and halal labeling and halal awareness simultaneously influence Korean Food purchasing decisions among gen-z Muslims in East Java. This shows that halal awareness can have an influence, while halal labeling cannot influence East Java Muslim consumers' purchasing decisions for Korean Food products.